KONTRIBUSI SITI WALIDAH DALAM PENGEMBANGAN PENDIDIKAN ISLAM DI INDONESIA MELALUI MUHAMMADIYAH - Muthrofin, Khoirul; Muchtar, Nicky Estu Putu (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2023)
This study aims to explore the historical contributions and achievements of Nyai Ahmad Dahlan, also known as Siti Walidah, in the context of education and community development. This study examines her involvement in the founding and leadership of Aisyiyah, an organization focused on women's empowerment and social welfare. Through a comprehensive review of historical documents, biographies, and scholarly sources, this research provides an understanding of Nyai Ahmad Dahlan's initiatives, such as the establishment of educational institutions, support for girls' schools, promotion of literacy programs, and giving attention to poor and orphaned children. Research findings reveal that Nyai Ahmad Dahlan plays an important role in promoting education among women and empowering them to actively participate in society. His efforts are not only limited to theoretical discussions, but are reflected in concrete actions that have a positive impact on the lives of individuals and society. In addition, her leadership and guidance inspired many women to get involved in social and educational initiatives, which contributed to the overall development of society. This research highlights the enduring legacy of Nyai Ahmad Dahlan as an influential figure in Indonesian history, emphasizing the importance of her contributions in education, social welfare, and women's empowerment.